2011
DOI: 10.1074/jbc.m111.309377
|View full text |Cite
|
Sign up to set email alerts
|

Importin β1 Protein-mediated Nuclear Localization of Death Receptor 5 (DR5) Limits DR5/Tumor Necrosis Factor (TNF)-related Apoptosis-inducing Ligand (TRAIL)-induced Cell Death of Human Tumor Cells

Abstract: Background: Nuclear localization of DR5 was observed in TRAIL-resistant tumor cells in human. Results: TRAIL-resistant tumor cells were sensitized to TRAIL by knockdown of importin ␤1. Conclusion: Importin ␤1-mediated nuclear translocation of DR5 limits DR5/TRAIL-induced cell death of human tumor cells.Significance: This provides a novel strategy to improve the efficiency of recombinant TRAIL and anti-DR5 antibodies in cancer therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
55
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(60 citation statements)
references
References 44 publications
4
55
1
Order By: Relevance
“…In addition, large amounts of DR5 were localized in the nucleus in HeLa and HepG2 cells (62). We did confirm that CCB or ZER induces the increased expression of DR5 on the cell surface.…”
Section: Discussionsupporting
confidence: 74%
“…In addition, large amounts of DR5 were localized in the nucleus in HeLa and HepG2 cells (62). We did confirm that CCB or ZER induces the increased expression of DR5 on the cell surface.…”
Section: Discussionsupporting
confidence: 74%
“…However, little is known about the underlying molecular mechanisms. A recent study identified two nuclear localization signals in DR5 protein which mediates its nuclear localization through the nuclear import pathway by importin beta1 in Hela and HepG2 cells (32). The overexpression of DRs in cytoplasm may reflect receptor-ligand internalization, a rapid process occurring after ligand binding.…”
Section: Discussionmentioning
confidence: 99%
“…Importin‐β‐mediated nuclear import of the death receptor DR5 limits the cell death of cancer cell lines. The DU145 prostate carcinoma cell line, which does not express nuclear DR5, is highly sensitive to the apoptosis‐inducing ligand TRAIL, whereas HeLa and HepG2 cells, which contain a large amount of nuclear DR5, are resistant to TRAIL . Importin‐7‐dependent nuclear import of the transcription factor Egr1, which regulates the expression of the tumor suppressor PTEN, is involved in tumor suppression.…”
Section: Imp‐βs In Pathologymentioning
confidence: 99%